Prolonged drug release from hot melt extruded solid dosage forms for oral application - Ramos, Filipa do Nascimento (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2020, Universidade de Lisboa, Faculdade de Farmácia.